Characterization of Pediatric In-Hospital Cardiopulmonary Resuscitation Quality Metrics Across an International Resuscitation Collaborative*. Issue 5 (May 2018) - Niles, Dana E.; Duval-Arnould, Jordan; Skellett, Sophie; Knight, Lynda; Su, Felice; Raymond, Tia T.; Sweberg, Todd; Sen, Anita I.; Atkins, Dianne L.; Friess, Stuart H.; de Caen, Allan R.; Kurosawa, Hiroshi; et al.
Abstract : Objectives: Pediatric in-hospital cardiac arrest cardiopulmonary resuscitation quality metrics have been reported in few children less than 8 years. Our objective was to characterize chest compression fraction, rate, depth, and compliance with 2015 American Heart Association guidelines across multiple pediatric hospitals. Design: Retrospective observational study of data from a multicenter resuscitation quality collaborative from October 2015 to April 2017. Setting: Twelve pediatric hospitals across United States, Canada, and Europe. Patients: In-hospital cardiac arrest patients (age < 18 yr) with quantitative cardiopulmonary resuscitation data recordings. Interventions: None. Measurements and Main Results: There were 112 events yielding 2, 046 evaluable 60-second epochs of cardiopulmonary resuscitation (196, 669 chest compression). Event cardiopulmonary resuscitation metric summaries (median [interquartile range]) by age: less than 1 year (38/112): chest compression fraction 0.88 (0.61–0.98), chest compression rate 119/min (110–129), and chest compression depth 2.3 cm (1.9–3.0 cm); for 1 to less than 8 years (42/112): chest compression fraction 0.94 (0.79–1.00), chest compression rate 117/min (110–124), and chest compression depth 3.8 cm (2.9–4.6 cm); for 8 to less than 18 years (32/112): chest compression fraction 0.94 (0.85–1.00), chest compression rate 117/min (110–123), chest compression depth 5.5 cm (4.0–6.5 cm). "Compliance" with guideline targets for 60-second chest compression "epochs" was predefined: chest compression fraction greater than 0.80, chest compression rate 100–120/min, and chest compression depth: greater than or equal to 3.4 cm in less than 1 year, greater than or equal to 4.4 cm in 1 to less than 8 years, and 4.5 to less than 6.6 cm in 8 to less than 18 years. Proportion of less than 1 year, 1 to less than 8 years, and 8 to less than 18 years events with greater than or equal to 60% of 60-second epochs meeting compliance (respectively): chest compression fraction was 53%, 81%, and 78%; chest compression rate was 32%, 50%, and 63%; chest compression depth was 13%, 19%, and 44%. For all events combined, total compliance (meeting all three guideline targets) was 10% (11/112). Conclusions: Across an international pediatric resuscitation collaborative, we characterized the landscape of pediatric in-hospital cardiac arrest chest compression quality metrics and found that they often do not meet 2015 American Heart Association guidelines. Guideline compliance for rate and depth in children less than 18 years is poor, with the greatest difficulty in achieving chest compression depth targets in younger children. Abstract : Supplemental Digital Content is available in the text.